Gender reporting guidelines in Italian public universities for assessing SDG 5 in the international context - Manuela Lucchese; Ferdinando Di Carlo; Natalia Aversano; Giuseppe Sannino; Paolo Tartaglia Polcini (Administrative Sciences, 2022)
Gender equity is a topic of significant interest for universities, who are called upon to plan strategies and measures to increase gender equality in line with international policies. With a qualitative methodology based on manual content analysis, the paper aims to understand whether and how this report could positively assess a university's actions for reaching SDG 5. This study's results show that the CRUI guidelines can be used by universities to disclose gender policies that may be of interest to stakeholders, and can also be synthesized in THE ranking, increasing university visibility. The present study could be helpful for universities, regulatory bodies, policy makers, and agency rankings to help them identify the most relevant gender items on which to focus their attention.
Keywords: 350; SDG 5; gender reporting; gender budgeting; Italian university; CSR; the impact ranking; social accounting theories; CRUI guidelines